Different functionalization of the internal and external surfaces in mesoporous materials for biosensing applications using "click" chemistry - Guan, B.; Ciampi, Simone; Le Saux, G.; Gaus, K.; Reece, P.; Gooding, J. (American Chemical Society, 2011)
We report the use of copper(I)-catalyzed alkyne-azide cycloaddition reaction (CuAAC) to selectively functionalize the internal and external surfaces of mesoporous materials. Porous silicon rugate filters with narrow line width reflectivity peaks were employed to demonstrate this selective surface functionalization approach. Hydrosilylation of a dialkyne species, 1,8-nonadiyne, was performed to stabilize the freshly fabricated porous silicon rugate filters against oxidation and to allow for further chemical derivatization via "click"CuAAC reactions. The external surface was modified through CuAAC reactions performed in the absence of nitrogen-based CuI-stabilizing species (i.e., ligand-free reactions). To subsequently modify the interior pore surface, stabilization of the Cu I catalyst was required. Optical reflectivity measurements, water contact angle measurements, Fourier transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS) were used to demonstrate the ability of the derivatization approach to selectively modify mesoporous materials with different surface chemistry on the exterior and interior surfaces. Furthermore, porous silicon rugate filters modified externally with the cell-adhesive peptide Gly-Arg-Gly-Asp-Ser (GRGDS) allowed for cell adhesion via formation of focal adhesion points. Results presented here demonstrate a general approach to selectively modify mesoporous silicon samples with potential applications for cell-based biosensing. © 2010 American Chemical Society.